ANALYSIS OF MOTOR POWER ELECTRIC MIRROR CONSUMPTION (xxxx-xxxx, 2024)
Electric mirrors, also known as electric rearview mirrors, are a system on vehicles that can move the outside rearview mirror electrically using a DC motor and switch. This allows the driver to adjust the rear view angle simply by opening the car window and changing it manually. However, inadequate learning facilities and resources often become obstacles to increasing understanding and knowledge. The method used is the ADDIE method. Existing Obstacles, Research Results In the final stage of the research process, it is intended to conclude the results of the research carried out, specifications for an Electric mirror motor with a voltage of 12 V and an electric current of 1.5 A, the results of calculating the required Electric mirror motor power of 18 watts. From the calculation results, it is found that the pump resistance is 8 Ω, with the resulting specifications being a voltage of 12V and an electric current of 1.5A.Keywords: electric mirror, ADDIE, DC motor, research, electric current.